EVALUATING THE COMPUTER BASE NATIONAL SCIENCE OLYMPIAD IMPLEMENTATION AT SENIOR HIGH SCHOOL LEVEL: A CIPP MODEL ANALYSIS - Marwa Halim; Awal Kurnia Putra Nasution; Sahat Siagian; Harun Sitompul; Muktar; Zulkifli Matondang (STMIK TIME, 2026)
The digital transformation in education has encouraged changes in national evaluation systems and academic competitions, including the implementation of the online-based National Science Olympiad (OSN). This study aims to evaluate the implementation of the online National Science Olympiad at the senior high school level using the CIPP (Context, Input, Process, Product) evaluation model. The study employed a mixed methods approach by collecting data through questionnaires, interviews, observations, and documentation studies. The participants consisted of student contestants, supervising teachers, school operators, and school management representatives. The findings indicate that, from the context aspect, the program is relevant to the needs of educational digitalization and implementation efficiency. From the input aspect, disparities were still found in infrastructure, internet network quality, and digital competencies among schools. From the process aspect, the program implementation generally ran well despite several technical constraints and variations in supervision quality. From the product aspect, the program improved accessibility and efficiency; however, it also generated perceptions of unfairness among some participants. The study concludes that the implementation of the online OSN is relatively effective, but it still requires improvements in infrastructure, technical standardization, and the integrity of the evaluation system. These findings contribute to the development of fairer and more sustainable digital academic competition policies.